Optimalisasi Implementasi Kurikulum Pai Secara Inovatif dan Adaptif - Marwan Kurniawan Rahim; Yahya Obaid; Herman Herman; Samsuri Samsuri (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2026)
Curriculum implementation is a crucial stage in determining the success of the educational process, particularly in Islamic Religious Education (IRE), which focuses not only on cognitive development but also on the formation of students' character and spiritual values. Amid rapid technological advancements and social changes, the implementation of the IRE curriculum is required to be more innovative and adaptive to remain relevant to students' needs. This study aims to examine strategies for optimizing the implementation of the IRE curriculum through innovative and adaptive approaches. The method employed is a literature review by analyzing various sources related to curriculum development, educational innovation, and IRE learning practices. The findings indicate that the optimization of IRE curriculum implementation can be achieved through the integration of technology in learning, the application of contextual learning approaches, and the strengthening of character education based on Islamic values. Furthermore, enhancing teachers' competencies and fostering collaboration among schools, parents, and communities are essential factors supporting successful curriculum implementation. Nevertheless, several challenges remain, including limited facilities and infrastructure, resistance to change, and the diverse backgrounds of students. Therefore, systematic and sustainable strategies are needed to address these obstacles effectively. Through innovative and adaptive curriculum implementation, IRE learning is expected to produce students who are not only intellectually competent but also possess strong character, noble morals, and the ability to face future life challenges.